MASALAH TRANSPORTASI FUZZY BILANGAN TRAPEZOIDAL DENGAN METODE ZERO POINT - Endang Listyanti Pratiwi (Jurnal Matematika, 2016)
ABSTRACT. A fuzzy transportation problem is a transportation problem in which the transportation cost, supply and demand quantities are fuzzy numbers. For solving fuzzy transportation problem, the parameter in fuzzy number must be converted to a crisp number. This thesis explores Zero Point method for finding a fuzzy optimal solution for a fuzzy transportation problem where the parameters are trapezoidal fuzzy numbers. Roubast Ranking is used for assertion of trapezoidal fuzzy numbers. To determine the optimal solution of fuzzy transportation problem with Zero Point method can be solved in two ways and from that will be obtained the same solution.